Breast Care Education for Breastfeeding Mothers to Increase Breast Milk Flow - Neneng Fitria Ningsih; Devi Eka Safitri (Global Sustainability Research Institute, 2026)
Breast care is an important preventive and promotive effort to support the smooth production of breast milk and prevent various breastfeeding problems such as sore nipples, engorgement, mastitis, and breast engorgement. Lack of knowledge and skills among breastfeeding mothers regarding proper breast care techniques is often a factor inhibiting the success of exclusive breastfeeding. This condition can reduce maternal motivation and increase the risk of early cessation of breastfeeding. Therefore, systematic and applicable education is needed to increase the capacity of mothers to perform breast care independently. This community service activity aims to improve the knowledge and skills of breastfeeding mothers in implementing proper breast care techniques. The method used is a participatory educational approach through interactive counseling, demonstrations, hands-on practice with assistance, discussions, and evaluation using pre- and post-tests. The results of the activity showed a significant increase in the knowledge, skills, and confidence of participants in practicing breast care. This activity effectively supports the success of exclusive breastfeeding and contributes to the sustainable improvement of maternal and infant health.